2014
DOI: 10.1161/circep.113.001289
|View full text |Cite
|
Sign up to set email alerts
|

Human Atrial Fibrillation Initiates via Organized Rather Than Disorganized Mechanisms

Abstract: Background It is unknown how atrial fibrillation (AF) is actually initiated by triggers. Based on consistencies in atrial structure and function in individual patients between episodes of AF, we hypothesized that human AF initiates when triggers interact with deterministic properties of the atria and may engage organized mechanisms. Methods and Results In 31 AF patients we mapped AF initiation after spontaneous triggers or programmed stimulation. We used 64-pole basket catheters to measure regional dynamic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 29 publications
1
47
0
Order By: Relevance
“…7 Conversely, if electrodes are too closely spaced, calculated wave propagation may fall within measurement error. For instance, for atrial conduction velocity in AF patients of 40 cm/sec, 31,59 reported errors in assigning onset time in AF (≈5-10 ms) translate to a distance of 2-4 mm (=40×0.005 to 40×0.010). Closer electrode separation than this will be attempting to identify circuits within measurement noise, and will have less confidence.…”
Section: Areas For Technical Improvement In Source-guided Ablation Of Afmentioning
confidence: 99%
“…7 Conversely, if electrodes are too closely spaced, calculated wave propagation may fall within measurement error. For instance, for atrial conduction velocity in AF patients of 40 cm/sec, 31,59 reported errors in assigning onset time in AF (≈5-10 ms) translate to a distance of 2-4 mm (=40×0.005 to 40×0.010). Closer electrode separation than this will be attempting to identify circuits within measurement noise, and will have less confidence.…”
Section: Areas For Technical Improvement In Source-guided Ablation Of Afmentioning
confidence: 99%
“…26 This has been the basis of physiological filtering employed in FIRM mapping to separate principal components from noise. 27 …”
Section: Separating Local From Far-field Activationmentioning
confidence: 99%
“…1 Maria Niespialolwska-Steuden*, 2 Vias Markides, 3 Osita Okafor, 3 Mohamed Farag, 3 Nikolaos Spinthakis, 3 Monika Cisecka, 2 Diana Adrienne Gorog, 2 Background Atrial fibrillation (AF) is the most frequent sustained cardiac arrhythmia and a major cause of morbidity and mortality. Catheter ablation is a potentially curative treatment.…”
Section: Improvement In Endogenous Thrombolytic Status Following Succmentioning
confidence: 99%